A Note on the Curious Case of John Bale in Spain. (16th September 2020) - Dominguez, Freddy C
Abstract: A slender folder at the Archivo Histórico Nacional in Madrid contains parts of a story about how John Bale's Illustrium majoris Britanniae scriptorum … summarium (1548) ended up in sixteenth century Spain. Inquisition documents from 1583 reveal how the book got to Toledo from Lyon and how the Holy Office came to know about it. By briefly telling this story, this short note hopes to pique interest in the documents and to suggest ways in which the archives in which they reside can support further research on censorship and the early-modern book trade.